Translationally Controlled Tumour Protein (TCTP) is present in human cornea and increases in herpetic keratitis - Batisti Cinzia; Ambrosio Maria R; Rocca Bruno J; Tosi Gian M; Sanchez Jean C; Arcuri Felice; Cintorino Marcella; Tripodi Sergio A (BMC, 2012)
Abstract Background Translationally Controlled Tumour protein is a multifunctional calcium binding protein which has an important role in apoptosis, calcium levels balance and immunological response. The aim of this study was to evaluated the presence and distribution of TCTP in healthy human corneas and to identify and characterize the presence and distribution of this protein in human normal cornea. Since recent studies suggest that apoptosis, calcium levels and immunological mechanisms play a role in the pathogenesis of herpetic stromal keratitis, we studied TCTP expression in this disease. Methods We evaluated the expression of TCTP at both RNA messanger and protein level by using reverse transcriptase analysis, immunoblotting and immunohistochemistry in 10 healthy samples cornea: four obtained after penetrating keratoplasty and six from eyes enucleated for other pathologies. Finally, we analysed by immunohistochemistry ten paraffin-embedded samples of Herpes simplex virus keratitis collected at Siena Department of Human Pathology and Oncology: 5 had clinically quiescent disease and 5 had active corneal inflammation. Results Reverse transcriptase and immunoblotting demonstrated TCTP expression in cornea as a 22,000 Da molecular weight band corresponding to the molecular weight of this protein. Immunohistochemically, all the layers of normal corneal epithelium showed TCTP cytoplasmic expression. TCTP was, also, observed in keratocytes and in the endothelium. In Herpes simplex virus keratitis samples, strong expression of TCTP was evident in stromal cells, in the inflammatory infiltrate and in neo-vessels. Conclusions In this preliminary study we demonstrated, for the first time, the presence of TCTP in human cornea, suggesting a potential role in the pathogenesis of herpes virus keratitis. Virtual Slides The virtual slide(s) for this article can be found here: http://www.diagnosticpathology.diagnomx.eu/vs/3306813447428149